2020
DOI: 10.1177/1467358420972156
|View full text |Cite
|
Sign up to set email alerts
|

The impact of transactional and transformational leadership on employee intention to stay in deluxe hotels: Mediating role of organisational commitment

Abstract: This study examines the impact of both transformational leadership (TFL) and transactional leadership (TCL) on employee intention to stay (ITS) in deluxe hotels. It also examines the mediating role of organisational commitment (OC) in the relationship between leadership styles, i.e. TFL and TCL, and ITS. A pre-tested questionnaire survey was self-administered to front-line employees in deluxe hotels in Egypt, where these leadership styles were prominent. The key findings showed that TFL has more positive impac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
47
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 32 publications
(58 citation statements)
references
References 42 publications
9
47
0
2
Order By: Relevance
“…Turnover intention refers to the probability of an employee quitting his/her current job. Several predictors were identified for the turnover intention in hotels, including job insecurity [ 4 ] organizational justice in general [ 33 ], procedural justice [ 34 ] and distributive justice [ 4 ] in particular, sexual harassment and trust in superior [ 35 ], leadership style and organizational commitment [ 36 ], job satisfaction [ 37 ]. On the other side, turnover intention can r influence job performance [ 38 ] and the spread of deviant behaviour as well as social loafing behaviour [ 4 ].…”
Section: Hypothesis Development and Conceptual Frameworkmentioning
confidence: 99%
“…Turnover intention refers to the probability of an employee quitting his/her current job. Several predictors were identified for the turnover intention in hotels, including job insecurity [ 4 ] organizational justice in general [ 33 ], procedural justice [ 34 ] and distributive justice [ 4 ] in particular, sexual harassment and trust in superior [ 35 ], leadership style and organizational commitment [ 36 ], job satisfaction [ 37 ]. On the other side, turnover intention can r influence job performance [ 38 ] and the spread of deviant behaviour as well as social loafing behaviour [ 4 ].…”
Section: Hypothesis Development and Conceptual Frameworkmentioning
confidence: 99%
“…Hospitality is among the top industries that suffers from high turnover due to the low image of the industry with poor compensation [ 36 , 37 ]. Studies on employee turnover in the hospitality industry have shown several predictors for employee turnover intention, such as organizational support [ 38 ]; organizational citizenship behavior [ 39 ]; organizational justice [ 40 ]; job satisfaction and organizational commitment [ 41 ]; coworkers and job security [ 27 ]; and leadership style and organisztional commitment [ 42 ].…”
Section: Literature Review and Hypothesis Buildingmentioning
confidence: 99%
“…Previous research (see for example, Deery and Jago 2015; Gui et al 2020;Sobaih et al 2022) have shown that leaders with transformational leadership characteristics have a significant influence on worker attitudes and behaviors. Therefore, the relationship between transformational leadership with other organizational attributes have drawn the attention of researchers in last few decades.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the relationship between transformational leadership with other organizational attributes have drawn the attention of researchers in last few decades. Earlier studies indicated a positive influence of transformational leadership on different job outcomes such as job satisfaction (Medley and Larochelle 1995); workers' motivation (Masi and Cooke 2000); organization effectiveness (Lowe et al 1996); organizational learning (Zagoršek et al 2009); psychological capital (Gom et al 2021); and intention to stay (Sobaih et al 2022). However, there is limited published research, to the best of the research team's knowledge, examining the relationship between transformational leadership and turnover intention amid COVID-19 on hotel workers through the effect of psychological safety.…”
Section: Introductionmentioning
confidence: 99%